2008
DOI: 10.1038/ng.95
|View full text |Cite
|
Sign up to set email alerts
|

DNA deletions and clonal mutations drive premature aging in mitochondrial mutator mice

Abstract: Mitochondrial DNA (mtDNA) mutations are thought to have a causal role in many age-related pathologies. Here we identify mtDNA deletions as a driving force behind the premature aging phenotype of mitochondrial mutator mice, and provide evidence for a homology-directed DNA repair mechanism in mitochondria that is directly linked to the formation of mtDNA deletions. In addition, our results demonstrate that the rate at which mtDNA mutations reach phenotypic expression differs markedly among tissues, which may be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
325
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 365 publications
(340 citation statements)
references
References 15 publications
13
325
1
1
Order By: Relevance
“…We found that heart, skeletal muscle, and duodenum tissues of 15-month-old rescued mnd2 mice contained many COX-negative cells ( COX-negative cells have also been described in brain tissues from premature aging mice. 36 However, we did not detect COX-negative cells in brain tissue sections of rescued mnd2 mice or their heterozygous mnd2/ 镁 ;Tg littermates (Supplementary Figure 4), demonstrating that the lack of HtrA2 activity is responsible for the COX deficiency in nonneuronal tissues.…”
Section: Loss Of Htra2 Results In Increased Mtdna Deletionsmentioning
confidence: 94%
See 1 more Smart Citation
“…We found that heart, skeletal muscle, and duodenum tissues of 15-month-old rescued mnd2 mice contained many COX-negative cells ( COX-negative cells have also been described in brain tissues from premature aging mice. 36 However, we did not detect COX-negative cells in brain tissue sections of rescued mnd2 mice or their heterozygous mnd2/ 镁 ;Tg littermates (Supplementary Figure 4), demonstrating that the lack of HtrA2 activity is responsible for the COX deficiency in nonneuronal tissues.…”
Section: Loss Of Htra2 Results In Increased Mtdna Deletionsmentioning
confidence: 94%
“…These results indicate that HtrA2 deficiency in non-neuronal tissues causes increased clonally expanded mtDNA deletions, which are believed to be a major contributing factor leading to premature aging and decreased life span. 2,3,36 Loss of HtrA2 causes increased autophagosome activity. Increased autophagy has been observed in premature aging mice.…”
Section: Loss Of Htra2 Results In Increased Mtdna Deletionsmentioning
confidence: 99%
“…First, it is possible that PolG and Tw + mice do not recapitulate the same mechanisms that accelerate or protect against loss of mitochondrial function seen in normal aging, respectively. In particular, the rate at which mtDNA mutations reach phenotypic expression differs markedly among tissues (Vermulst et聽al., 2008) and vessels might be protected from these manipulations. However, aging at/after 44聽wk was associated with a marked reduction in mtCN and mitochondrial respiration, while Tw + mice maintained mtCN and respiration at 44 and 72聽wk to levels seen in younger mice.…”
Section: Discussionmentioning
confidence: 99%
“…Ageing is a major risk factor for heart failure and mitochondrial dysfunction is also central to theories of ageing. Mitochondrial function and mitochondrial DNA (mtDNA) quality were shown to decline with age in postmitotic tissues [14][15][16][17] , and several recent studies, reporting on defects in mtDNA quality control mechanisms in mice, have shown that these mutant animals develop a phenotype of premature aging 17,18 . Given these findings, mitochondrial quality control may be associated with aging-related decreases in cardiac contractility and the pathogenesis of specific heart diseases that are especially caused by mitochondrial dysfunction including doxorubicin (DOX)-induced cardiotoxicity 19 .…”
mentioning
confidence: 99%